Facile synthesis of ZnOHF/ZIF‐8 composite coating for corrosion protection of Zn–Cu–Ti alloy. (26th April 2022) - Ni, Ya; Zhu, Dongdong; Qi, Jiqiu; Zhu, Lei
Abstract: ZnOHF/ZIF‐8 (Zeolitic Imidazolate Frameworks‐8) composite with a thickness of about 13.4 μm was coated on Zn–Cu–Ti alloy via hydrothermal route for the first time and its corrosion resistance performance was investigated in 3.5% NaCl solution. It is found that the I corr of the composite‐coated alloy (7.03 × 10 –4 A/cm 2 ) is lower than that of alloy substrate (12.47 × 10 –4 A/cm 2 ). Meanwhile, the composite‐coated alloy shows a higher corrosion product resistance of 121.2 Ω cm 2 in comparison with that of the alloy substrate (102.2 Ω cm 2 ). Moreover, after 6 days of immersion, the composite‐coated alloy exhibits a lower corrosion layer thickness. Its coating and corrosion layer is only about 42.5 μm, but for the alloy substrate this value is 67 μm. This work confirms the ZnOHF/ZIF‐8 composite can be used as an effective anti‐corrosion coating for Zn alloy.